Chemical Constituents of Cupressus sempervirens L. cv. Cereiformis Rehd. Essential Oils: Essential Oils of Cupressus semipervirens L.cv. - Emamia, Sayyed Ahmad; Hassanzadeh Khayyat, Mohammad; Rahimizadeh, M.; Fazly-Bazzaz, Bibi Seddigheh; Assilia, J. (Iranian Journal of Pharmaceutical Sciences, 2005)
The essential oils obtained from fresh fruits and terminal branchlets with adherent leaves of Cupressus sempervirens L. cv. Cereiformis Rehd. growing in Iran, were analyzed by GC-MS, and screened for bacteriostatic and fungistatic activities. Thirteen components were identified in the essential oils. The main constituents of both fruits and leaves were ?-pinene, Æ-3-carene, ?-terpenyl acetate and terpinolene. The essential oil of leaves and fruits showed no antimicrobial activity against, Bacillus subtilis, Candida albicans, Escherichia coli and Staphylococcus aureus. The defatted ethanolic extract of leaves and fruits were examined for the presence of alkaloids, flavonoides, and saponins. The nonvolatile compounds in leaves and fruits were quite rich in tannins and flavonoids but the amounts of alkaloids and saponins were not significant.